PENGGUNAAN EJAAN SKRIPSI MAHASISWA FISIP TAHUN 2011 DAN IMPLIKASINYA PADA MKU BINDO - Sepirna Juwita Putri; Nurlaksana Eko Rusminto; Kahfie Nazaruddin (FKIP Universitas Lampung, 2013)
The research problem of this study is student’s punctuation scripts of Social and Political Sciences Faculty at the Lampung University in 2011 academic year. The aim is to describe how pungtuation in their scripts. While there are 168 scripts, only 10 scripts were taken as the data source. Using documentation to yield data, the present researcher purposively select three pages out of each chapter of any script. In the case of insufficient pages, the whole chapter will be selected. Based on data analysis, the researcher found that there are accuracy as well as inaccuracy in students pungtuation. Based on error analysis through surface strategy taxonomy, it was found that there are mistakes in omission, addition, and misformation.Keywords: script, pungtuation, student